1983
DOI: 10.1139/y83-149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrial natriuretic factor on renal handling of water and electrolytes in rats

Abstract: The intravenous injection of an extract of atrial myocardium into anesthetized rats during a hypotonic diuresis resulted in an increase in the renal excretion of water, sodium, potassium, calcium, magnesium, and phosphate. There was an increase in urine concentration which was probably a result of the secretion of vasopressin since it did not occur in Brattleboro (di/di) rats. A transient increase in glomerular filtration rate and renal plasma flow occurred during the first five minutes with a more sustained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…It has been reported that intravenous injection of atrial extracts produces a diuresis and kaliuresis of short duration (de Bold et al 1981;Borenstein et al 1983 ;Keeler and Azzarolo 1983 ;Vaughan et al 1983 ;Thibault et al 1984). These discrepancies of duration of diuresis and kaliuresis between in our experiment and in others might have been caused by the different volume status of animals.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…It has been reported that intravenous injection of atrial extracts produces a diuresis and kaliuresis of short duration (de Bold et al 1981;Borenstein et al 1983 ;Keeler and Azzarolo 1983 ;Vaughan et al 1983 ;Thibault et al 1984). These discrepancies of duration of diuresis and kaliuresis between in our experiment and in others might have been caused by the different volume status of animals.…”
Section: Resultscontrasting
confidence: 42%
“…However, glomerular filtration rate may have increased immediately after the intravenous injection of a-hANP, and this increase in GFR may have been transient, therefore, resulting in failure of determination for a period of 30 min after the a-hANP injection. In fact, Keeler and Azzarolo (1983) reported an increase in GFR only during the first 5-min period following the injection of atrial extract in spite of a fall in mean arterial pressure. There have been some different reports concerning the effects of atrial extracts on GFR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last few years, a vasodilatory, natriuretic compound derived from granules within cardiocytes of the right atrium has been described (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). This substance has been very recently characterized as a closely related group of peptides of 21-26 amino acids (2-4) derived from a common precursor polypeptide of 152 amino acids (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…But the mechanism by which atrial extract or atrial natriuretic peptide produces a natriuresis and diuresis is still unclear. Some studies have suggested that contribution of an increase in renal blood flow (Keeler and Azzarolo 1983;Wakitani et al 1985) or glomerular filtration rate Maack et al 1984 ; Beasley and Malvin 1985;Huang et al 1985) to the natriuresis and diuresis, and others have indicated direct tubular effects (Briggs et al 1982; Sonnenberg et al 1982; Pollock and Banks 1983; Burnett et al 1984Burnett et al , 1986Hammond et al 1985).…”
mentioning
confidence: 99%